The Role of Expressive Writing Interventions in Decreasing Trauma Symptoms and Increasing Meaning - Okonkwo, Adaeze; Dlamini, Thandiwe (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to examine the effectiveness of an expressive writing intervention in decreasing trauma symptoms and increasing perceived meaning among individuals who have experienced traumatic events. Methods and Materials: A randomized controlled trial was conducted with 30 participants from South Africa, who were randomly assigned to either an intervention group (n = 15) or a control group (n = 15). The intervention group participated in eight structured 75-minute expressive writing sessions over a four-week period, while the control group received no psychological treatment. Standardized measures were used to assess trauma symptoms (Impact of Event Scale-Revised) and perceived meaning (Meaning in Life Questionnaire) at three stages: pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures analysis of variance (ANOVA), with Bonferroni post-hoc tests for pairwise comparisons. Statistical analysis was performed using SPSS version 27. Findings: Results indicated a significant interaction effect between time and group for both trauma symptoms (F(2,56) = 27.08, p < .001, partial η² = .488) and meaning (F(2,56) = 31.34, p < .001, partial η² = .528). The intervention group demonstrated a substantial reduction in trauma symptoms from pre-test (M = 61.47, SD = 5.83) to post-test (M = 45.80, SD = 6.11), with further improvement at follow-up (M = 42.93, SD = 5.62). Perceived meaning significantly increased from pre-test (M = 18.40, SD = 3.55) to post-test (M = 25.87, SD = 3.66) and follow-up (M = 28.60, SD = 3.20). No significant changes were observed in the control group for either variable. Conclusion: Expressive writing significantly reduces trauma symptoms and enhances meaning-making in individuals exposed to trauma, with effects sustained over a five-month period, suggesting its potential as a cost-effective intervention for trauma recovery.